Optimization of Gampong Pageu in Preventing Sexual Crime in Children in Kabupaten Bireuen - Zuriah Zuriah; Syah Iskandar (An-Nisa': Journal of Gender Studies, 2022)
The purpose of this study is to examine how Pageu Gampong is optimized in preventing sexual crimes against children in Aceh and what are the challenges in optimizing Pageu Gampong in preventing sexual crimes against children in Aceh, especially in Bireuen District. This research is descriptive qualitative research with a juridical-normative-empirical approach. The data collection technique was carried out by interviewing village apparatus/equipment in the village of Juli Tambo Tanjong as one of the villages that became the object of this research. Further data collection was carried out by means of a documentation study by collecting legal archives and Qanuns as support. The results of the study show that the optimization of Pageu Gampong in preventing sexual crimes in Bireuen Regency is carried out in two ways. First, as a preventive measure for village officials, Juli Tambo, who is part of the Gampong Pageu, makes and implements the Gampong Qanun in a comprehensive manner. Second, by repressive method, namely, if there is a sexual crime against children in the territorial area of Gampong  Juli and the perpetrator is known, then the Gampong apparatus who are members of the Gampong  Pageu will immediately follow up and forward it to the Bireuen Police. Then the challenge in the implementation of Pageu Gampong  is that the role of Pageu Gampong  is only limited to assisting victims without escorting cases until a judge's decision is made, with limited time, budget, and manpower from the Pageu Gampong itself.